Logística reversa para substituição de combustíveis na indústria cimenteira por coprocessamento em forno de clinquer - Junior, Nelson Kadel (Universidade do Vale do Rio dos Sinos, 2012)
This dissertation aims to study a waste co-processing, and develop a way to make it economically sustainable within the logistic and reverse logistics theory. This brings together results that go beyond the financial area, when the logistics chains in the region are used at best in order to reduce the impact on the environment. Once this research project has already been identified in its development phase, the method of research is action-research. In this type of method, they use existing theories to plan interventions in the field, while the results take advantage to generate theorist advancements. The specific aims of this paper target the study, firstly, of the waste suppliers, analyzing their locations as well as the kinds of available products. From this point of view, we can see the best place to install the production blend plant, taking into consideration the environmental restrictions, the costs and the offering of different types of transport, and finally it analyzes the cement consumer companies of such blend. The most important results are related to the changing of the co-processing plant location, the logistic process of waste collection as well as the final product and the development of a kind of suitable wrapping for its transport. The final consequences are environmental, financial and strategic. This project enables the use of a significant portion of waste that would previously have as destination, at best, the region's landfills, and are now being useful as fuels in a new production chain. Since the economic results achieved two major companies studied. For the first, there was a 27% reduction in logistics costs of products produced. As for the second, 8% of the cost of fuel. Finally, the strategic guarantee, for the blending unit, a differential to possible new entrants in the market. So, this study analyses the concepts on logistics and reverse-logistics, making an overview on the cement production and the different kinds of fuel used in these plants, with its future replacement options - once this is a type of industry that demands high amounts of energy and heating. Finally, the case study talks about the first co-processing plant in Rio Grande do Sul, which is going to use several sorts of waste in the manufacturing of an alternative kind of fuel for clinker kilns.
Keywords: Logística; Logística reversa; Produção de cimento; Combustíveis; Coprocessamento; Pesquisa-ação; Logistic; Reverse logistic; Cement production; Fuels; Co-processing; Action research; ACCNPQ::Engenharias::Engenharia de Produção